Uma leitura straussiana do Teeteto, 152a - Souza, Roberto Solino de (2016)
This work examines the possibility that Socrates is attacking a straw man in the Theaetetus, 152a, when he explains Protagoras's dictum that “man is the measure of all things” as embracing a vulgar form of relativism which takes knowledge as being merely perception. It begins with Leo Strauss’s suggestion that the great writers of the past made use of a peculiar technique, that he names metaphorically as “writing between the lines,” aiming to protect their heterodox views from political persecution while expressing openly other views that conform to generally accepted opinion. It seeks to demonstrate that Strauss’s suggestion is a valid one and that writing between the lines was recognized throughout most Philosophy’s history and only recently forgotten. It also seeks to clarify Strauss’s suggestion and identify a minimal set of rules to guide the reading of that Theaetetus’s passage. In the end, it considers that reading between the lines of the said passage can point to the conclusion that the examined hypothesis is correct and suggests the so called “Digression” (172c– 177c) as a starting point from where to begin a Straussian interpretation of the dialog as a whole.